A polyethylene biofilter and its application in rural sewage resource utilization
By rationally preparing a variety of materials and technical treatments in polyethylene resin biofilter tubes, it can maintain structural integrity and have high water permeability under high pressure, and solve the problem of easy damage and surface opening of traditional blind groove materials under high pressure. The problem of low rate has achieved effective treatment and resource utilization of sewage.
Patent Information
- Application Number
- CN202411764920.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-04
Smart Images

Figure CN119240925B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sewage resource utilization, and in particular to a polyethylene biofilter tube and application thereof in rural sewage resource utilization. Background Art
[0002] As the living standards of villagers continue to improve, villagers have higher sensory requirements for water use, such as "color, smell, and transparency". In addition, the content of high-molecular organic matter in the composition of gray water is high, and the absorption and utilization rate of plants is low. At present, blind ditches or perforated pipes are mainly used for infiltration and water distribution. Traditional blind ditch materials have many limitations in practical applications. For example, the cost of traditional sand and gravel blind ditches is relatively low, and they can play a certain role in some simple water seepage scenarios, but the pipes of traditional sand and gravel blind ditches are easily damaged under high pressure, resulting in water seepage failure. Sand-free concrete pipes have good stability and can withstand the pressure of soil to a certain extent. The manufacturing process of mesh resin pipes and perforated hard pipes is relatively mature and convenient to produce; however, the surface opening rate of sand-free concrete pipes, mesh resin pipes, and perforated hard pipes is low, and the general opening rate is far less than 5 times that of perforated pipes, and the water collection capacity is limited. Although soft permeable pipes have certain flexibility, they have poor durability and are inconvenient to construct. These problems make the effect of traditional blind ditches in water seepage projects unsatisfactory. Traditional water distribution, plastic pipes, mesh tubes, graded sand and gravel, etc., mainly pass water through the voids, and sewage can easily grow anaerobic film in the gaps, causing blockage.
[0003] The main components of traditional biofilters are polymers, such as polyethylene (PE), polypropylene (PP), polystyrene (PS), etc. These polymers have the following disadvantages: (1) The molecular structure of polymers is very stable and difficult to be decomposed by microorganisms. Microorganisms usually need specific enzymes to decompose organic matter, but they lack enzymes that can decompose plastic polymer chains. Therefore, plastics can exist for a long time in the natural environment without being degraded by microorganisms. (2) The surface of polymers usually has a low surface energy, which makes it difficult for microorganisms to attach to their surface. Microorganisms need to attach to solid surfaces to grow and reproduce, but the low surface energy of plastics makes it difficult for microorganisms to attach firmly. (3) Polymer materials are hydrophobic, that is, they do not dissolve in water. This makes it difficult for water to stay on the surface of plastics, which is necessary for the growth of microorganisms. Microorganisms need to be in a humid environment to grow and reproduce because water can provide dissolved nutrients, transport metabolites, and maintain cell structure. The hydrophobicity of plastics limits the presence of water, which is not conducive to the growth of microorganisms.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a polyethylene biofilter tube and its application in rural sewage resource utilization. The polyethylene biofilter tube has excellent compressive strength and water permeability, and its surface positively charged property enables it to adsorb microorganisms.
[0006] To achieve the above-mentioned object, the first aspect of the present application provides a polyethylene biofilter, comprising the following components in parts by weight: 75-92 parts of polyethylene resin, 5-20 parts of polycarbonate, 6-12 parts of needle-shaped wollastonite powder, 4-10 parts of polyether polyol, 2-8 parts of compatibilizer, 1-8 parts of chitosan quaternary ammonium salt, 0.5-3 parts of isophorone diisocyanate, and 1-5 parts of activated carbon;
[0007] The compatibilizer is POE grafted glycidyl methacrylate.
[0008] The present invention creatively combines the above-mentioned raw materials, takes polyethylene resin as the matrix, and obtains a polyethylene biofilter (plastic blind pipe) with excellent compressive strength and water permeability under the synergistic effect of polycarbonate, needle-shaped wollastonite powder, polyether polyol, compatibilizer, chitosan quaternary ammonium salt, isophorone diisocyanate and activated carbon. The polyethylene biofilter overcomes the shortcomings of traditional blind ditch and blind pipe materials. The positively charged surface of the polyethylene biofilter enables it to adsorb microorganisms, effectively provide microbial implantation, decompose microorganisms in sewage, and avoid pollution accumulation and clogging. At the same time, it has high compressive strength, and in a shallow buried resource utilization and consumption body covered with soil, the problem of biological filler failure due to extrusion and clogging is solved.
[0009] The polyethylene biofilter tube described in the present invention still maintains good structural integrity under dynamic load pressure. Generally, under a pressure of 200KPa, its compression rate is less than 15%. Even if it is compressed due to overload, due to its three-dimensional structure, the residual gap is more than 50%, and there is no problem of water blockage. This characteristic ensures that in various complex engineering environments, such as rural areas with complex terrain and uneven soil pressure, it can still play a stable drainage role and will not be crushed by soil pressure. At the same time, the surface opening rate of the polyethylene biofilter tube is high, which can quickly and effectively collect seepage water in the soil, and collect and drain it in time. The pollutants filtered and accumulated in the soil outside the filter tube are decomposed by the microbial flora attached to the surface of the filter tube, so that the pollutants in the water can be more effectively absorbed as plant nutrients.
[0010] In addition, the polyethylene biofilter tube of the present invention carries a positive charge, and an electrostatic attraction will be generated between the microorganisms with negative charge. This attraction is like the mutual attraction between the positive and negative poles of a magnet, which enables the microorganisms to approach and attach to the surface of the biological filler. The presence of positive charge will change the chemical properties and physical structure of the surface of the biological filler, so that some sites that are conducive to the attachment of microorganisms are formed on its surface. These sites can interact with the relevant groups or structures on the surface of the microorganisms to enhance the attachment of microorganisms to the surface of the filler. Positive charge will attract negatively charged microorganisms, thereby changing the distribution of microorganisms in the water body. This effect can increase the chance of contact between microorganisms and fillers and promote the adsorption of microorganisms on the filler. Promote the formation of biofilm: When microorganisms are adsorbed by the positive charge on the surface of the biological filler, they will gradually gather on the surface of the filler and form a biofilm. Biofilm is a complex structure formed by the interaction of microbial groups and attachment to the surface of the carrier. The positive charge on the surface of the biological filler is not only conducive to the initial attachment of microorganisms, but also can play a stabilizing and promoting role in the formation of the biofilm, so that the biofilm is more firmly attached to the filler.
[0011] Among them, under the specific polyethylene resin system of the present invention, the POE grafted glycidyl methacrylate (POE-g-GMA) contains POE and GMA, POE-g-GMA can effectively enhance the interaction between polyethylene and polycarbonate, improve the compatibility of the two, and improve the dispersibility and stability of the blending system. The POE grafted glycidyl methacrylate can form a covalent bond with polycarbonate grafting reaction, promote the formation of a chemical bonding bridge between polycarbonate, GMA and POE, and improve the interface. The polyether polyol molecule terminal contains a hydroxyl group, which can also react chemically with the epoxy group of GMA, so that the polyether polyol chain segment is interconnected with POE-g-GMA, thereby forming a cross-linked network between PC, PE and polyether polyol. The cross-linked network not only improves the compatibility of the composite material, but also reduces the phase separation tendency of the interface of each component through covalent bridging, avoiding the phase separation phenomenon between polyethylene, polycarbonate and polyether polyol; at the same time, PC, polyether polyol and POE-g-GMA all contain polar groups. Through the introduction of GMA, the polar groups of PC and polyether polyols are more likely to interact at the interface. The GMA-grafted POE has moderate polarity, which can not only interact with PC and polyether polyols, but also have a certain affinity with PE, and can promote the adhesion of activated carbon powder on the surface, so that the surface of the filter tube is positively charged, and it can also improve the interfacial tension between PC, PE and polyether polyols, and promote the attachment of microorganisms on the surface; in addition, due to the amphiphilic properties of POE-GMA (to polar PC and polyether polyols, and non-polar PE), POE-GMA can form a three-dimensional cross-linked structure at the interface. This cross-linked network links the molecular chains of PE, PC and polyether polyols through covalent bonds and polar interactions, making the structure of the ternary system more compact and stable, buffering and relieving local stress at the interface, and improving the compressive strength. The specific POE-g-GMA and PC of the present invention can refine the grains of PE, improve the crystallization behavior of PE, and promote the formation of uniform and nano-scale and micron-scale dispersed phase structures, thereby effectively improving the compressive strength and water permeability of the system.
[0012] Among them, needle-shaped wollastonite powder has a high aspect ratio and can form physical support in the composite matrix, significantly improving the compressive strength of the material. Its unique structure makes the stress more evenly dispersed, reduces local stress concentration, and improves the bearing capacity of the filter tube. The surface of wollastonite powder can interact with polar components such as polyether polyols to form good interface adhesion, thereby enhancing the overall strength of the composite material. Especially in PC and PE, the presence of needle-shaped wollastonite powder forms a good rigid support and improves the compression rate of the composite material under pressure; chitosan quaternary ammonium salt has quaternary ammonium groups, which can interact with PC and polyether polyols through ionic bonds and hydrogen bonds, thereby improving the interfacial compatibility of the material, promoting the uniform distribution of stress, and improving the compressive performance. Its flexible molecular chain segments can act as stress buffers at the molecular level, reduce the formation of brittle cracks during compression deformation, and improve compressive strength. Needle-shaped wollastonite powder and chitosan quaternary ammonium salt can form a rigid-flexible composite reinforcement system. Wollastonite powder provides rigidity enhancement and improves compressive strength; the flexible toughening effect of chitosan quaternary ammonium salt effectively disperses stress and inhibits crack expansion during compression, so that the filter tube has more excellent compressive performance, and the needle-shaped wollastonite and the chitosan quaternary ammonium salt can improve the molding and processing performance, promote the formation of smoother polyethylene filaments, and reduce the friction resistance when water flows through the pipeline. The chitosan quaternary ammonium salt can form a good interface adhesion with PE, PC, and polyether polyols, so that the smoothness of the pipeline is further improved, thereby more effectively improving the compressive strength and water permeability.
[0013] Wherein, the amount of the polyethylene resin is 75 to 92 parts, for example, it can be 75 parts, 76 parts, 78 parts, 80 parts, 82 parts, 84 parts, 85 parts, 86 parts, 88 parts, 90 parts, 92 parts or a range consisting of any two of the values.
[0014] Wherein, the amount of the polycarbonate is 5 to 20 parts, for example, it can be 5 parts, 6 parts, 8 parts, 10 parts, 12 parts, 15 parts, 16 parts, 18 parts, 20 parts or a range consisting of any two of the values.
[0015] The amount of the needle-shaped wollastonite powder is 6 to 12 parts, for example, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts or a range consisting of any two of these values.
[0016] Wherein, the amount of the polyether polyol is 4 to 10 parts, for example, it can be 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or a range consisting of any two of the values.
[0017] The amount of the compatibilizer is 2 to 8 parts, for example, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or a range consisting of any two of these values.
[0018] Wherein, the dosage of the chitosan quaternary ammonium salt is 1 to 8 parts, for example, it can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or a range consisting of any two of the values.
[0019] The amount of isophorone diisocyanate used is 0.5 to 3 parts, for example, 0.5 parts, 1 part, 2 parts, 3 parts or a range consisting of any two of these values.
[0020] The amount of activated carbon used is 1 to 5 parts, for example, 1 part, 2 parts, 3 parts, 4 parts, 5 parts or a range consisting of any two of these values.
[0021] As an implementation scheme of the present application, the following components are included in parts by weight: 80 to 84 parts of polyethylene resin, 10 to 15 parts of polycarbonate, 8 to 10 parts of needle-shaped wollastonite powder, 6 to 8 parts of polyether polyol, 4 to 6 parts of compatibilizer, 2 to 5 parts of chitosan quaternary ammonium salt, 1 to 2 parts of isophorone diisocyanate, and 2 to 4 parts of activated carbon. In particular, when the amount of each raw material is within this range, the compatibility of each raw material is better, and the compressive strength and water permeability can be further improved.
[0022] As an implementation scheme of the present application, the viscosity of the polyether polyol at 25°C is 270~600mPa·s, the molecular weight is 2000~3000, and the hydroxyl value is 36~57.5mgKOH / g. In particular, the polyether polyol using such parameters has better compatibility in the system, can promote the formation of a cross-linked network structure, and further improve the compressive strength and water permeability.
[0023] As an implementation scheme of the present application, the polycarbonate has a melt flow rate of 10 to 20 g / 10 min at 300°C / 1.2 kg according to the ISO1133-2011 method, for example, it can be 10 g / 10 min, 12 g / 10 min, 14 g / 10 min, 15 g / 10 min, 16 g / 10 min, 18 g / 10 min, 20 g / 10 min or a range consisting of any two of these values. By controlling the melt flow rate of the polycarbonate within this range, it is possible to more effectively promote the formation of a three-dimensional cross-linked network, promote the adhesion of activated carbon powder on the surface, and effectively improve the compressive strength and water permeability of the system.
[0024] As an embodiment of the present application, the particle size of the chitosan quaternary ammonium salt is 400-500 mesh, for example, it can be 400 mesh, 450 mesh, 500 mesh or a range consisting of any two values thereof. By controlling the particle size of the chitosan quaternary ammonium salt within this range, it can have a better stress buffering effect, reduce the formation of brittle cracks during compression deformation, form good interface adhesion with PE, PC, and polyether polyols, and further improve the smoothness of the pipeline, thereby more effectively improving the compressive strength and water permeability.
[0025] As an implementation scheme of the present application, the POE grafted glycidyl methacrylate has a melt flow rate of 3 to 5 g / 10 min at 190°C / 2.16 kg according to the ISO1133-2011 method, for example, 3 g / 10 min, 3.5 g / 10 min, 3.8 g / 10 min, 4 g / 10 min, 4.5 g / 10 min, 5 g / 10 min. By controlling the melt flow rate of the POE grafted glycidyl methacrylate within this range, it has better compatibility with PC and PE, can more effectively improve and enhance the interaction force between polyethylene and polycarbonate, improve the compatibility between the two, improve the dispersibility and stability of the blending system, avoid phase separation between polyethylene, polycarbonate and polyether polyol, and more effectively improve the compressive strength and water permeability of the system.
[0026] As an embodiment of the present application, the particle size of the needle-shaped wollastonite is 600-800 mesh, for example, it can be 600 mesh, 650 mesh, 700 mesh, 750 mesh, 800 mesh or a range consisting of any two values therein.
[0027] As an implementation scheme of the present application, the weight ratio of the needle-shaped wollastonite powder and the chitosan quaternary ammonium salt is (2~4):1. By controlling the weight ratio of the two within this range, it is possible to better promote the formation of a rigid-flexible composite reinforcement system, while improving the smoothness of the polyethylene filaments and reducing the friction resistance of water flowing through the pipeline. The chitosan quaternary ammonium salt can form good interface adhesion with PE, PC, and polyether polyols, thereby further improving the smoothness of the pipeline, thereby more effectively improving the compressive strength and water permeability.
[0028] As an embodiment of the present application, the weight ratio of the sum of the weight of the polyethylene resin and the polycarbonate to the compatibilizer is (16.5~20):1.
[0029] As an embodiment of the present application, the polyethylene resin has a melt flow rate of 0.2 to 0.55 g / 10 min at 190°C / 2.16 kg according to the ISO1133-2011 method, for example, it can be 0.2 g / 10 min, 0.21 g / 10 min, 0.25 g / 10 min, 0.3 g / 10 min, 0.35 g / 10 min, 0.4 g / 10 min, 0.45 g / 10 min, 0.55 g / 10 min, 0.55 g / 10 min or a range consisting of any two of the values.
[0030] As an embodiment of the present application, 0.5 to 2 parts by weight of a catalyst is also included.
[0031] As an embodiment of the present application, the catalyst includes at least one of dibutyltin dilaurate, dioctyltin dilaurate or di(dodecylthio)dibutyltin, and a Pt catalyst.
[0032] Preferably, the polyethylene biofilter tube of the present invention may further include at least one of an antioxidant, a colorant, and a flame retardant.
[0033] The polyethylene biofilter of the present invention may include an antioxidant. Suitable antioxidants include, but are not limited to, thioester antioxidants, hindered phenol antioxidants, phosphite antioxidants, phosphate antioxidants, and combinations thereof.
[0034] Preferably, the thioester antioxidant includes at least one of dialkyl thiodipropionate or pentaerythritol tetrakis (3-lauryl thiopropionate).
[0035] Preferably, the hindered phenol antioxidant includes at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanurate, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl alcohol ester, and ethylene bis(ethylene oxide)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate].
[0036] Preferably, the phosphite antioxidant includes at least one of tris(2,4-di-tert-butylphenyl)phosphite and pentaerythritol bis(2,4-tert-butylphenyl)phosphite.
[0037] Preferably, the phosphate antioxidant includes bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate.
[0038] The polyethylene biofilter of the present invention may include a lubricant, and suitable lubricants include but are not limited to hyperbranched polyester, stearate, ethylene bis stearamide, polyethylene wax and combinations thereof.
[0039] The polyethylene biofilter of the present invention may include a colorant, and suitable colorants include but are not limited to carbon black, titanium dioxide, zinc sulfide, iron red, titanium yellow and combinations thereof.
[0040] The second aspect of the present application provides a method for preparing a polyethylene biofilter tube, comprising the following steps:
[0041] (1) adding polyethylene resin, polyether polyol, isophorone diisocyanate, catalyst, and chitosan quaternary ammonium salt into an internal mixer and kneading to obtain a mixture; and uniformly mixing the mixture, polycarbonate, needle-shaped wollastonite powder, and a compatibilizer to obtain a precursor;
[0042] (2) The precursor material is melted in an extruder, and the melt is ejected through a spinneret hole of a melt-blowing die to obtain polyethylene filaments;
[0043] (3) Extruding the polyethylene filaments into a mold to obtain a filter tube body;
[0044] (4) The activated carbon is sprayed onto the surface of the filter tube body using pulsed high-voltage electrostatic spraying technology and cooled to obtain a polyethylene biofilter tube.
[0045] The present invention firstly carries out co-extrusion of substances other than activated carbon, carries out silk making to obtain polyethylene filaments, then extrude the polyethylene filaments into shape, heats them, and applies the activated carbon to the surface of the filter tube body by means of a pulsed high-voltage electrostatic sprayer, thereby obtaining a polyethylene biological filter tube with excellent compressive strength and water permeability and a positively charged surface. The polyethylene biological filter tube can not only effectively solve the problem of rural sewage treatment and reduce the pollution of sewage to the environment, but also realize the recycling of resources, reduce the energy consumption and water use costs in rural areas, promote the sustainable development of rural areas, and provide an efficient and reliable solution for rural ecological construction and environmental governance, and has broad application prospects and important practical significance.
[0046] As an embodiment of the present application, the mixing temperature in step (1) is 160-200°C;
[0047] The melting temperature in step (2) is 220-250°;
[0048] The spraying pressure in step (4) is 0.3-0.5 MPa, the frequency is 0.8-1.2 Hz, and the temperature is 180-200°C.
[0049] The third aspect of the present application provides an application of a polyethylene biofilter tube in rural sewage resource utilization.
[0050] The beneficial effects of the present invention are as follows: (1) The present invention uses polyethylene resin as a matrix, and under the synergistic effect of polycarbonate, needle-shaped wollastonite powder, polyether polyol, compatibilizer, chitosan quaternary ammonium salt, isophorone diisocyanate, and activated carbon, a polyethylene biofilter (plastic blind pipe) with excellent compressive strength and water permeability is obtained. The polyethylene biofilter overcomes the shortcomings of traditional blind ditch and blind pipe materials. The positive charge on its surface enables it to adsorb microorganisms, effectively provide microbial implantation, decompose microorganisms in sewage, and avoid pollution accumulation and blockage. At the same time, it has high compressive strength, and in shallow buried and covered resource utilization and consumption bodies, it solves the problem of biological filler failure due to extrusion and blockage. (2) The polyethylene biofilter described in the present invention can effectively solve the problem of rural sewage treatment, reduce the pollution of sewage to the environment, and can also realize the recycling of resources, reduce energy consumption and water costs in rural areas, promote the sustainable development of rural areas, and provide an efficient and reliable solution for rural ecological construction and environmental governance. It has broad application prospects and important practical significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 Dimensional drawing of the polyethylene biofilter tube of the present invention. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0053] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0054] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0055] The raw materials used in the embodiments and comparative examples are described as follows:
[0056] Polyethylene resin-1: melt flow rate at 190°C / 2.16kg is 0.3 g / 10 min, Dow Chemical, brand: XUS60921.01.
[0057] Polyethylene resin-2: melt flow rate at 190°C / 2.16kg is 0.55 g / 10 min, Dow Chemical, brand: XUS60921.01.
[0058] Polyethylene resin-3: melt flow rate at 190℃ / 2.16kg is 0.21g / 10min, Dow Chemical, brand: SI-LINK TM DFDA-5445.
[0059] Polyethylene resin-4: melt flow rate at 190°C / 2.16kg is 0.07 g / 10 min, Dow Chemical, brand: DGDA 2484 NT.
[0060] Polyethylene resin-5: melt flow rate at 190℃ / 2.16kg is 3.0g / 10min, Dow Chemical, brand: SI-LINK TM DFDB-5480 NT.
[0061] Polycarbonate-1: melt flow rate at 300°C / 1.2kg is 20 g / 10 min, Covestro, brand: PC2407.
[0062] Polycarbonate-2: melt flow rate at 300°C / 1.2kg is 10 g / 10 min, Covestro, brand: PC6557.
[0063] Polycarbonate-3: melt flow rate at 300°C / 1.2kg is 36 g / 10 min, Covestro, brand: PC1260.
[0064] Polycarbonate-4: melt flow rate at 300°C / 1.2kg is 6 g / 10 min, Covestro, brand: PC9425.
[0065] Needle-shaped wollastonite powder-1:600 mesh, Siyuan Mining.
[0066] Needle-shaped wollastonite powder-2: 800 mesh, Siyuan Mining.
[0067] Needle-shaped wollastonite powder-3: 1250 mesh, Siyuan Mining.
[0068] Needle-shaped wollastonite powder-4:325 mesh, Siyuan Mining.
[0069] Polyether polyol-1: The viscosity at 25°C is 270~370mPa·s, the molecular weight is 2000, the hydroxyl value is 54.5~57.5mgKOH / g, Bluestar Dongda, brand DL-2000D.
[0070] Polyether polyol-2: The viscosity at 25°C is 500~600mPa·s, the molecular weight is 3000, the hydroxyl value is 36~39mgKOH / g, Bluestar Dongda, brand DL-3000D.
[0071] Polyether polyol-3: The viscosity at 25°C is 60~80mPa·s, the molecular weight is 400, the hydroxyl value is 270~290mgKOH / g, Bluestar Dongda, brand DL-400D.
[0072] Polyether polyol-4: The viscosity at 25°C is 270~370mPa·s, the molecular weight is 4000, the hydroxyl value is 26.5~29.5mgKOH / g, Bluestar Dongda, brand DL-4000D.
[0073] Chitosan quaternary ammonium salt was purchased from Hehai Biological, and after grinding and sieving, chitosan quaternary ammonium salts 1-4 with different particle size distributions were obtained according to the mesh number of the sieve.
[0074] Chitosan quaternary ammonium salt-1:400 mesh.
[0075] Chitosan quaternary ammonium salt-2: 500 mesh.
[0076] Chitosan quaternary ammonium salt-3: 200 mesh.
[0077] Chitosan quaternary ammonium salt-4: 800 mesh.
[0078] POE-g-GMA-1: POE grafted with glycidyl methacrylate, with a melt flow rate of 3~5 g / 10min at 190℃ / 2.16kg, from Coase, brand W5A.
[0079] POE-g-GMA-2: POE grafted with glycidyl methacrylate, with a melt flow rate of 13-16 g / 10 min at 190°C / 2.16 kg, from Coase, brand W5F.
[0080] PE-g-MAH: PE grafted with maleic anhydride, Coase, brand W1L.
[0081] POE: Dow, brand POE8450.
[0082] Isophorone diisocyanate: commonly available on the market.
[0083] Activated carbon: 300 mesh, commonly available in the market.
[0084] Catalyst: dibutyltin dilaurate.
[0085] Talc: 400 mesh, commonly available in the market.
[0086] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0087] Examples 1 to 27, Comparative Examples 1 to 8
[0088] The formulations of the polyethylene biofilter tubes of Examples 1 to 27 and Comparative Examples 1 to 8 are shown in Table 1 and Table 2 (all in the tables are parts by weight).
[0089] The preparation methods of the polyethylene biofilter tubes of Examples 1 to 27 and Comparative Examples 1 to 8 all include the following steps:
[0090] (1) adding polyethylene resin, polyether polyol, isophorone diisocyanate, catalyst, and chitosan quaternary ammonium salt into an internal mixer and kneading to obtain a mixture; and uniformly mixing the mixture, polycarbonate, needle-shaped wollastonite powder, and polyethylene grafted glycidyl methacrylate to obtain a precursor;
[0091] (2) The precursor material is melted at 220-250°C in an extruder (the aspect ratio of the extruder is 20), and the melt is ejected through a spinneret hole (with a diameter of 150 mm) of a melt-blowing die to obtain polyethylene filaments;
[0092] (3) Place the polyethylene filaments according to Figure 1 The size of the filter tube is extruded by a die to obtain a filter tube body;
[0093] (4) Use pulsed high-voltage electrostatic spraying technology to spray activated carbon onto the surface of the filter tube body, cool it, and obtain a polyethylene biofilter tube. The spraying pressure is 0.4 MPa, the frequency is 1 Hz, and the temperature is 200°C.
[0094] Table 1
[0095]
[0096] Table 2
[0097]
[0098] Performance Testing
[0099] 1. The compressive performance is tested in accordance with GB / T9647-2003; the pipe is placed horizontally on the pressure plate of the ring stiffness testing machine, and the pipe that meets the test requirements is loaded at a loading rate of 8 mm per minute. Two parallel pressure plates are used to apply pressure to the pipe in a vertical direction. When the deformation in the diameter direction of the pipe cross-sectional area is 4% of the inner diameter of the pipe sample, the value is recorded.
[0100] 2. Test the porosity of the tube according to WDF-189-5488-0555.
[0101] 3. Test the compression rate of the tube at a pressure of 200Kpa.
[0102] Table 3
[0103]
[0104] It can be seen from Table 3 that the polyethylene biofilter tube of the present invention has excellent compressive strength and water permeability, wherein the ring stiffness of the polyethylene biofilter tube is ≥15.25KN / m 2 The compression rate under 200Kpa pressure is ≤8.53%, and the surface porosity is between 86~94%.
[0105] Comparative Examples 1 to 4 and Comparative Examples 6 to 7 show that the present invention significantly improves the compressive strength and water permeability of the polyethylene biofilter by controlling the amount of each raw material to: 75 to 92 parts of polyethylene resin, 5 to 20 parts of polycarbonate, 6 to 12 parts of needle-shaped wollastonite powder, 4 to 10 parts of polyether polyol, 2 to 8 parts of compatibilizer, 1 to 8 parts of chitosan quaternary ammonium salt, 0.5 to 3 parts of isocyanate, and 1 to 5 parts of activated carbon.
[0106] By comparing Examples 2 and 3 with Examples 1 and 4, it can be seen that the present invention further improves the compressive strength and water permeability of the polyethylene biofilter by controlling the amount of each raw material to: 80-84 parts of polyethylene resin, 10-15 parts of polycarbonate, 8-10 parts of needle-shaped wollastonite powder, 6-8 parts of polyether polyol, 4-6 parts of compatibilizer, 2-5 parts of chitosan quaternary ammonium salt, 1-2 parts of isocyanate, and 2-4 parts of activated carbon.
[0107] Comparative Examples 3, 5 to 8 show that the present invention further improves the compressive strength and water permeability of the polyethylene biofilter by controlling the melt flow rate of the polyethylene resin at 190°C / 2.16kg to 0.2-0.55g / 10min.
[0108] Comparative Examples 3, 9 to 11 show that the present invention further improves the compressive strength and water permeability of the polyethylene biofilter by controlling the melt flow rate of polycarbonate at 300°C / 1.2kg to 10 to 20g / 10min.
[0109] By comparing Examples 3 and 12 to 14, it can be seen that the present invention further improves the compressive strength and water permeability of the polyethylene biofilter by controlling the particle size of the needle-shaped wollastonite powder to be 600 to 800 meshes.
[0110] Comparative Examples 3 and 15-17 show that the present invention further improves the compressive strength and water permeability of the polyethylene biofilter by controlling the viscosity of the polyether polyol at 25°C to 270-600 mPa·s, the molecular weight to 2000-3000, and the hydroxyl value to 36-57.5 mgKOH / g.
[0111] By comparing Examples 3 and 18 to 20, it can be seen that the present invention further improves the compressive strength and water permeability of the polyethylene biofilter by controlling the particle size of the chitosan quaternary ammonium salt to 400 to 500 meshes.
[0112] By comparing Example 3 and Example 21, it can be seen that the present invention further improves the compressive strength and water permeability of the polyethylene biofilter tube by controlling the melt flow rate of the POE grafted GMA at 190°C / 2.16kg to 3-5 g / 10min.
[0113] By comparing Example 3 with Examples 22 to 24, it can be seen that the present invention further improves the compressive strength and water permeability of the polyethylene biofilter by controlling the weight ratio of needle-shaped wollastonite powder to chitosan quaternary ammonium salt to (2 to 4):1.
[0114] By comparing Example 3 with Examples 25 to 27, it can be seen that the present invention further improves the compressive strength and water permeability of the polyethylene biofilter by controlling the weight ratio of the sum of the weight of the polyethylene resin and the polycarbonate to the compatibilizer to be (16.5 to 20):1.
[0115] By comparing Example 3 with Comparative Examples 1 to 3, it can be seen that the present invention adopts POE grafted GMA as a compatibilizer, which significantly improves the compressive strength and water permeability of the polyethylene biofilter tube.
[0116] By comparing Example 3 with Comparative Examples 4 to 6, it can be seen that the needle-shaped wollastonite powder and the chitosan quaternary ammonium salt of the present invention have a certain synergistic effect in improving the compressive strength and water permeability.
[0117] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polyethylene biofilter, characterized in that: The method comprises the following raw materials in parts by weight: 75-92 parts of polyethylene resin, 5-20 parts of polycarbonate, 6-12 parts of needle-shaped wollastonite powder, 4-10 parts of polyether polyol, 2-8 parts of compatibilizer, 1-8 parts of chitosan quaternary ammonium salt, 0.5-3 parts of isophorone diisocyanate and 1-5 parts of activated carbon; The compatibilizer is POE grafted glycidyl methacrylate.
2. The polyethylene biofilter according to claim 1, characterized in that: The preparation method comprises the following raw materials in parts by weight: 80-84 parts of polyethylene resin, 10-15 parts of polycarbonate, 8-10 parts of needle-shaped wollastonite powder, 6-8 parts of polyether polyol, 4-6 parts of compatibilizer, 2-5 parts of chitosan quaternary ammonium salt, 1-2 parts of isophorone diisocyanate and 2-4 parts of activated carbon.
3. The polyethylene biofilter according to claim 1, characterized in that: The polyether polyol has a viscosity of 270-600 mPa·s at 25° C., a molecular weight of 2000-3000, and a hydroxyl value of 36-57.5 mgKOH / g.
4. The polyethylene biofilter according to claim 1, characterized in that: The polycarbonate has a melt flow rate of 10-20 g / 10 min under the conditions of 300° C. / 1.2 kg.
5. The polyethylene biofilter according to claim 1, characterized in that: The particle size of the chitosan quaternary ammonium salt is 400-500 meshes.
6. The polyethylene biofilter according to claim 1, characterized in that: The melt flow rate of the POE grafted glycidyl methacrylate at 190° C. / 2.16 kg is 3-5 g / 10 min.
7. The polyethylene biofilter according to claim 1, characterized in that: The particle size of the needle-shaped wollastonite powder is 600-800 meshes.
8. The polyethylene biofilter according to claim 1, characterized in that: The weight ratio of the needle-shaped wollastonite powder to the chitosan quaternary ammonium salt is (2-4):
1.
9. The polyethylene biofilter according to claim 1, characterized in that: The weight ratio of the sum of the weight of the polyethylene resin and the polycarbonate to the compatibilizer is (16.5-20):
1.
10. The polyethylene biofilter according to claim 1, characterized in that: The melt flow rate of the polyethylene resin at 190° C. / 2.16 kg is 0.2-0.55 g / 10 min.
11. The polyethylene biofilter according to claim 1, characterized in that: Also includes 0.5 to 2 parts by weight of a catalyst.
12. The polyethylene biofilter according to claim 11, characterized in that: The catalyst includes at least one of dibutyltin dilaurate, dioctyltin dilaurate, di(dodecylthio)dibutyltin, and Pt catalyst.
13. The method for preparing the polyethylene biofilter tube according to any one of claims 11 to 12, characterized in that: The following steps are involved: (1) adding polyethylene resin, polyether polyol, isophorone diisocyanate, catalyst, and chitosan quaternary ammonium salt into an internal mixer and kneading to obtain a mixture; and uniformly mixing the mixture, polycarbonate, needle-shaped wollastonite powder, and a compatibilizer to obtain a precursor; (2) The precursor material is melted in an extruder, and the melt is ejected through a spinneret hole of a melt-blowing die to obtain polyethylene filaments; (3) Extruding the polyethylene filaments into a mold to obtain a filter tube body; (4) The activated carbon is sprayed onto the surface of the filter tube body using pulsed high-voltage electrostatic spraying technology and cooled to obtain a polyethylene biofilter tube.
14. The method for preparing a polyethylene biofilter according to claim 13, characterized in that: The mixing temperature in step (1) is 160-200°C; The melting temperature in step (2) is 220-250°C; The spraying pressure in step (4) is 0.3-0.5 MPa, the frequency is 0.8-1.2 Hz, and the temperature is 180-200°C.
15. Use of the polyethylene biofilter tube according to any one of claims 1 to 12 in rural sewage resource utilization.
Citation Information
Patent Citations
Method for filtering mail messages for a plurality of client computers connected to a mail service system
US6092101A
TPU (Thermoplastic Polyurethane Elastomer) material capable of being used for drinking water pipe and preparation method of TPU material
CN107828037A
Polyethylene composite material with high mechanical property and high environmental stress cracking resistance as well as preparation method and application of polyethylene composite material
CN116003892A